Pengaruh Suhu dan Ion Logam Terhadap Potensi Senyawa Kompleks Ditiokarbamat Sebagai Zat Aditif Pada Pelumas - Dian Ranggina; Zakiyah Darajat; Muhammad Arham Yunus; Nurfiansyah Nurfiansyah (Universitas Pahlawan Tuanku Tambusai, 2022)
The ideal quality of lubricant can be obtained by adding additives. One of the functions of additives in lubricants is to maintain viscosity against temperature changes. Dithiocarbamate complexes with heavy metals have very low solubility in water so that dithiocarbamate compounds have great potential as additives in lubricants. This research was conducted in an effort to determine the effect of temperature (40 oC and 100 oC) on the viscosity of the lubricant and metal ions (Mn2+, Fe3+, Co2+) in the synthesis of dithiocarbamate complex compounds on their potential as additives in lubricants. This compound was synthesized by in situ method and to measure and compare the viscosity of the lubricant before and after the addition of the complex compound as an additive.The results showed that complex compounds from N-ethylisopropylditiocarbamate ligands could be synthesized with metal ions Mn(II), Fe(III) and Co(II). Where is the synthesis of complex compounds obtained yields Mn(II)-N-ethylisopropylditiocarbamate amounted to 49.59%, Fe(III)-N-Ethylisopropyldithiocarbamate of 41.81%,and Co(II)-N-Etilisopropil ditiocarbamate by64.12%.From the results of the characterization of the viscosity test, it can be seen that temperature and metal ions in complex compounds affect their potential effectiveness as additives in lubricants. Of the three complex compounds it is more effective at 100 oC than 40 oC, where metal ions Mn (II) are more effective than Fe(III) and Co (II). Keywords: Lubricants, additives, metal ions, temperature, dithiocarbamate.